PENGARUH PENERAPAN GOOD GOVERNANCE DAN AUDIT KINERJA TERHADAP AKUNTABILITAS KEUANGAN PEMERINTAH DAERAH - Ora, Maria Sri Angelina Ruku Sare; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to examine the influence of good governance, and performance audit, to the financeaccountability. The population is local apparatus working unit in Surabaya and the sample collection techniquehas been done by using purposive sampling and 74 people have been obtained samples. The data analysistechnique has been carried out by using multiple linear regressions method.The result of the test shows thatindependent variables which consist of the implementation of good governance and performance audit givesimultaneously influence to the State Finance Accountability, This result indicates that the fluctuation of StateFinance Accountability of local apparatus working unit in Surabaya depend on how well the good governanceand performance audit which has been applied by the institution. This result is supported by the contributionwhich has given by those variable to the State Finance Accountibility of local apparatus working unit inSurabaya i.e. 32,4% whereas the remaining is 67.6% has been contributed by other factors. The result of partialtest shows that each of the implementation variable of good governance and audit performance, give positive andsignificant influence to the state finance accountability. The result indicates that when the implementation ofgood governance, and audit performance, it will improve the state finance accountability.Keywords: the implementation of good governance, performance audit, state finance accountability.